Application of Preference Selection Index (PSI) Method for Decision Support System in Evaluating Supervisor Candidates of the Kitchen Department at Grand Antares Hotel - Hutahaean, Yosefa Fras; Sinurat, Sinar; Syahputra, Ridwa (Cattleya Darmaya Fortuna, 2025)
In the Supervisor Candidate Assessment at the Grand Antares Hotel, the criteria used to determine Supervisor Candidates at the Grand Antares Hotel are made based on criteria. Based on the results of the research that has been conducted, the Preference Selection Index Method is applied in the assessment of supervisor candidates who will be appointed as supervisors, then 4 criteria are determined: Education, Skills, Work Experience. GPA Data analysis is carried out so that criteria can be determined from existing alternatives and weighted using the Preference Selection Index (PSI) Method.